FOSTERING NATIONAL IDENTITY COMPETENCIES IN YOUNG PEOPLE AS A SOCIAL PEDAGOGICAL AND PSYCHOLOGICAL NECESSITY - Nigmanova Umida Bahromovna (Scholar Express Journal, 2022)
The article deals with issues related to the socio-pedagogical and psychological features of the development of competencies of national identity among young people in the context of globalization of spiritual and ideological processes. In a number of speeches, resolutions and decrees of Sh. Mirziyoyev, much attention was paid to solving priority tasks in instilling in young people the spirit of respect for national and spiritual values, instilling in them the qualities of national self-consciousness. The analysis gave a very good, new understanding of various aspects of the factors of national identity. The main conclusions and proposals related to the analysis of national selfconsciousness, national ideas and spirituality are put forward.
Keywords: Globalization; Media; Personality